Combined Behavior of Reinforced Concrete Out-of-Plane Parts Beams Encased with Steel Section - Hasan M. A. Albegmprli; Doaa T. Hashim; Muthanna A. N. Abbu (Buildings, 2025)
This research investigated and compared the structural behavior of reinforced concrete straight beams and beams made with out-of-plane parts. This study focused on the influence of the location and number of out-of-plane parts, as well as encasing the beams with a steel section, on the ultimate strength, deflection, and rotation in addition to the ductility, energy absorption, and failure mode. A total of nine beams were modelized numerically, divided into three series. The first one included one straight beam, while the remaining two series included four beams each made with out-of-plane parts with and without steel sections. The beams with out-of-plane parts connected the two, three, four, and five concrete segments. The outcomes revealed that the beams made with out-of-plane parts showed less strength than straight beams, which increased the connected segments and reduced the ultimate strength capacity. The regular beam’s linearity was dissimilar to the zigzag beams, which showed a linearity of 32% and was reduced to 22%, 20%, 19.67%, and 16% for beam out-of-plane parts made with two, three, four, and five segments, respectively. Forming a zigzag in the plane of the beams reduced the cracking load, but the decrement depended on the number of parts, which led to more reduction in the yielding load. Concerning the deflection and deformations, the concrete straight beams failed in flexure, with maximum deflection occurring at the midspan of the beam, which was different for beams without plane parts, which showed a combined shear-torsional failure for which the maximum deformation occurred at the midspan with inclination of connected parts on the interior perpendicular axis. Encasing the beams’ out-of-plane parts with steel sections enhanced the structural behavior. The ductility and energy absorption of the out-of-plane parts beams were less than the straight ones, but encasing the beams with a steel section improved the ductility and energy absorption twice.